Assessment of Low-Cost Tide Gauges to Meet GLOSS 1-cm Precision and Accuracy Standards: A Case Study on Pramuka Island, Indonesia - Zulfikar Adlan Nadzir; Irdam Adil (Forum Geografi)
The expansion of the tide gauge network along the coasts is essential for better monitoring of sea-level dynamics. Owing to climate change, the urgency has been exacerbated, especially during the last two decades. However, densification a challenging task because of the lack of affordability of the sensor, especially in the Global South. Further, the precision and accuracy requirements of 1-cm imposed by the Global Sea Level Observing System (GLOSS) is too restrictive, particularly for low-cost tide gauge sensors. Here, we evaluated the performance of a low-cost DIY tide gauge in meeting these standards. Three sets of sea level observations from IR-TIDES, a DIY tide gauge sensor observed in 2016 and 2018, were subjected to a performance test in terms of precision and accuracy in comparison with a global tide model and two neighbouring established tide gauges. All three datasets were estimated to have an 8- cm standard deviation as a metric for the precision level. In terms of accuracy, the IR-TIDES datasets had a standard deviation of 25 cm and a correlation coefficient of 0.616. Overall, IR-TIDES demonstrated sufficient precision while still lacking accuracy, partially meeting the GLOSS quality standard. These findings could strengthen the confidence level of a low-cost DIY tide gauge, especially for use as a back-up and redundant sensor for an established tide gauge station after ad-dressing the limitations.